NAVIGATING HUMAN RESILIENCE: AN ANALYSIS OF INTERNAL AND EXTERNAL LIFE STRUGGLES IN DANIELLE STEEL’S ZOYA - Puspita, Nana Dewi; Pratiwy, Devi; Pardi, Pardi (Universitas Islam Sumatera Utara, 2025)
This study explores the multidimensional nature of human resilience as portrayed in Danielle Steel’s novel Zoya, focusing on the protagonist’s psychological and sociological transformation amid historical upheaval. Employing Braun and Isaac’s (1979) tripartite model of life struggle—conflict with self, others, and the environment—and integrating Maslow’s (1970) hierarchy of needs alongside Self-Determination Theory (Deci & Ryan, 2000), the research analyzes how Zoya navigates personal trauma, intergenerational tension, and socio-political displacement. Set against the backdrop of the Russian Revolution and global migrations of the 20th century, Zoya’s journey from aristocratic exile to self-reliant immigrant underscores the interplay of intrinsic motivation—such as identity reconstruction and emotional autonomy—and extrinsic forces like war, poverty, and social change. Through qualitative literary analysis, the study uncovers how Zoya redefines dignity, agency, and meaning across shifting cultural landscapes. The findings suggest that Steel’s narrative transcends conventional romance, offering a compelling literary case study of adaptive resilience. By merging literary analysis with psychological and sociological theory, this article contributes to broader interdisciplinary discourses on trauma, survival, and the evolving female bildungsroman. Zoya’s evolution serves not only as a fictional reflection of resilience but also as a universal narrative of human tenacity amid crisis.